18F-FDG PET/CT imaging in pulmonary sarcomatoid carcinoma - Luo, Zhe-Huang; Luo, Xiao-Yan; Qi, Wan-Ling; Liu, Qian (Frontiers in Oncology, 2024)
Background: Pulmonary sarcomatoid carcinoma (PSC) is a rare highly aggressive and poorly differentiated non-small cell carcinoma, and little is known about the information on the usefulness of 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT). We investigated the clinical and 18 F-FDG PET/CT features of PSC.We retrospectively analyzed 25 consecutive PSC patients who had undergone 18 F-FDG PET/CT. Demographic data. PET/CT findings before treatment, pathological features, and prognosis in these patients were investigated to define correlates between maximal standard uptake value (SUVmax) and clinicopathological parameters.Results: From March 2017 to January 2023, twenty-five eligible patients with PSC were identified. There were 23 (92%) men, aged 68.5±8.5 (range 56-90) years. Eighteen (72%) patients had a frequent smoking history. The mean size of PSCs was 59.3±18.6 (range 29-97) mm, and 23 (92%) PSCs were Stage IV tumors. 20 (80%) lesions were located in the upper lung and 19 (76%) cases belonged to the peripheral type. Necrotic foci appeared in 21(84%) tumors. 11 (44%) PSCs invaded the pleura. All PSCs were FDG avid, and the mean of SUVmax was 11.8±5.3 (range 4.8-25.5). Metastases were found on PET/CT in 24(96%) patients. The SUVmax of the lesions ≥ 5cm was higher than that of the lesions < 5cm (p=0.004), and the SUVmax of lesions with TTF-1 expression was higher than those of lesions without TTF-1 expression (p=0.009). All of the 25 primary lesions were considered malignant and confirmative, probable, and possible diagnosis of PSC was made in 2 (8%), 4 (16%), and 5(20%) patients, respectively on PET/CT. PSC was not considered in 14 (56%) patients, in PET/CT. The survival of patients with surgery didn't demonstrate a significantly good prognosis as compared with those without surgery (p=0.675).Conclusions: All PSCs had obvious FDG avidity. Although imaging diagnosis is still difficult, combined clinical and imaging features more than 40% of primary lesions were considered for the possibility of PSC in our group. Early histopathological diagnosis is necessary to help develop a reasonable regimen.